A Prospective, Randomized, Controlled Study to Evaluate the Effectiveness of a Fabric-Based Wireless Electroceutical Dressing Compared to Standard-of-Care Treatment Against Acute Trauma and Burn Wound Biofilm Infection - Chan, Rodney K; Nuutila, Kristo; Mathew-Steiner, Shomita S; Diaz, Victoria; Anselmo, Kristin; Batchinsky, Maria; Carlsson, Anders; Ghosh, Nandini; Sen, Chandan K; Roy, Sashwati (Advances in wound care (New Rochelle, N.Y.), 2024)
Despite advances in the use of topical and parenteral antimicrobial therapy and the practice of early tangential burn wound excision to manage bacterial load, 60% of the mortality from burns is attributed to bacterial biofilm infection. A low electric field (∼1 V) generated by the novel FDA-cleared wireless electroceutical dressing (WED) was previously shown to significantly prevent and disrupt burn biofilm infection in preclinical studies. Based on this observation, the purpose of this clinical trial was to evaluate the efficacy of the WED dressing powered by a silver-zinc electrocouple in the prevention and disruption of biofilm infection. : A prospective, randomized, controlled, single-center clinical trial was performed to evaluate the efficacy of the WED compared with standard-of-care (SoC) dressing to treat biofilms. Burn wounds were randomized to receive either SoC or WED. Biopsies were collected on days 0 and 7 for histology, scanning electron microscopy (SEM) examination of biofilm, and for quantitative bacteriological analyses. In total, 38 subjects were enrolled in the study. In 52% of the WED-treated wounds, little to no biofilm could be detected by SEM. WED significantly lowered or prevented increase of biofilm in all wounds compared with the pair-matched SoC-treated wounds. WED is a simple, easy, and rapid method to protect the wound while also inhibiting infection. It is activated by a moist environment and the electrical field induces transient and micromolar amounts of superoxide anion radicals that will prevent bacterial growth. WED decreased biofilm infection better compared with SoC. The study was registered in clinicaltrials.gov as NCT04079998.